2022
DOI: 10.1029/2021ef002351
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Variability of Winter Warm Arctic‐Cold Eurasia Dipole Patterns Modulated by Pacific Decadal Oscillation and Atlantic Multidecadal Oscillation

Abstract: A prominent feature of Northern Hemisphere (NH) climate variations in recent decades is the warm Arctic-cold Eurasia (WACE) pattern in winter surface air temperature (SAT) (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Therefore, our atmospheric model results due to the stochastic SST forcing are in a manner compatible with previous studies based on satellite products and high-resolution simulations (Bishop et al, 2017;Kirtman et al, 2012;Small, Bryan, et al, 2019. Recent studies suggested that the PDO warm phase is conductive to the formation of "warm Arctic and cold Eurasia" pattern (Kim et al, 2020;Li et al, 2020;Luo et al, 2022;Screen & Francis, 2016;Tokinaga et al, 2017). Reanalysis data shows that during PDO warm phase, 500 hPa geopotential height anomalies basically exhibit an Arctic Oscillation negative phase, and along with the Arctic warming, Eurasia continent is getting colder than normal at high latitudes warmer than normal in midlatitudes (Figure 13a).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, our atmospheric model results due to the stochastic SST forcing are in a manner compatible with previous studies based on satellite products and high-resolution simulations (Bishop et al, 2017;Kirtman et al, 2012;Small, Bryan, et al, 2019. Recent studies suggested that the PDO warm phase is conductive to the formation of "warm Arctic and cold Eurasia" pattern (Kim et al, 2020;Li et al, 2020;Luo et al, 2022;Screen & Francis, 2016;Tokinaga et al, 2017). Reanalysis data shows that during PDO warm phase, 500 hPa geopotential height anomalies basically exhibit an Arctic Oscillation negative phase, and along with the Arctic warming, Eurasia continent is getting colder than normal at high latitudes warmer than normal in midlatitudes (Figure 13a).…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies suggested that the PDO warm phase is conductive to the formation of “warm Arctic and cold Eurasia” pattern (Kim et al., 2020; Li et al., 2020; Luo et al., 2022; Screen & Francis, 2016; Tokinaga et al., 2017). Reanalysis data shows that during PDO warm phase, 500 hPa geopotential height anomalies basically exhibit an Arctic Oscillation negative phase, and along with the Arctic warming, Eurasia continent is getting colder than normal at high latitudes and warmer than normal in midlatitudes (Figure 13a).…”
Section: Discussionmentioning
confidence: 99%
“…The significant negative correlations indicate that as winter anticyclone activities in Siberia intensify, temperatures in the mid‐latitudes of Eurasia, especially in Siberia, are likely to become low with a higher risk of the appearance of low‐temperature events. These results can be linked with the winter temperature change factors by previous studies, such as the East Asian winter monsoon (Wang and Lu, 2016), the Atlantic multidecadal oscillation (Luo et al ., 2017a; 2017b; 2022) and phase of the Arctic Oscillation (Woo et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…If confirmed, this result would suggest that the North Atlantic heat transported to the Arctic would not be as determinant in sea ice changes in the Chukchi Sea. Very recently Luo et al (2022) further highlighted the joint effect of AMO and PDO on the decadal variability of Arctic air temperatures. The loss of summer Arctic sea ice and flushing of multi-layer sea ice out of basin in the past decade has already changed the atmospheric circulation.…”
Section: Links With the Amo And Amocmentioning
confidence: 99%